2019
DOI: 10.1002/widm.1327
|View full text |Cite
|
Sign up to set email alerts
|

No Free Lunch Theorem for concept drift detection in streaming data classification: A review

Abstract: Many real‐world data mining applications have to deal with unlabeled streaming data. They are unlabeled because the sheer volume of the stream makes it impractical to label a significant portion of the data. The data streams can evolve over time and these changes are called concept drifts. Concept drifts have different characteristics, which can be used to categorize them into different types. A trade‐off between performance and cost exists among many concept drift detection approaches. On the one hand, high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 96 publications
1
31
0
1
Order By: Relevance
“…The successful design of an effective detector is not straightforward, yet it is primordial to achieve a more reliable system. The way to find the best strategy for concept drift detection still remains an open research issue, as confirmed in [36]. This challenge to find the best universal solution becomes evident in the most recent comparison among drift detectors carried out by [37].…”
Section: Concept Drift Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful design of an effective detector is not straightforward, yet it is primordial to achieve a more reliable system. The way to find the best strategy for concept drift detection still remains an open research issue, as confirmed in [36]. This challenge to find the best universal solution becomes evident in the most recent comparison among drift detectors carried out by [37].…”
Section: Concept Drift Detectionmentioning
confidence: 99%
“…Consequently, drift detection turns into a relevant factor for those active mechanisms that need a triggering mechanism to perform an adaptation after drift occurs [36]. A drift detector should estimate the time instant at which change occurs over the data stream so that when the detection appears, the adaptation mechanism is applied to the base learner in order to avoid the degradation of its predictive performance.…”
Section: Concept Drift Detectionmentioning
confidence: 99%
“…The generation mechanism also allows easy alteration of dataset dimensionality. To demonstrate the ability of HRDD to handle high-dimensional data, we considered d = [5,10,15,20,30,40]. Data generation details can be found in Table 3.…”
Section: Experiments 1: Understanding Hrddmentioning
confidence: 99%
“…Various detection methods have been proposed to explicitly mark out the drifts [4], [5]. Nonetheless,…”
Section: Introductionmentioning
confidence: 99%
“…Numerous algorithms are proposed for managing concept drift. [82,154] review the generic algorithms to handle the concept drift. There are two main detection methods, performance-based and data distribution-based.…”
Section: Data Collectionmentioning
confidence: 99%